Annual Meeting of Presidents and Administrators of Superior Courts of Justice 2012. Declaration of The Presidents of The Higher Courts of Justice of The Country - s.a, s.a (2012)
The undersigned, Presidents of the Superior Courts of Justice of the country who subscribe, gathered at the Meeting of Presidents and Administrators of Superior Courts of Justice 2012,